Growth performance of white, black and bronze color heritage turkeys under semi-intensive system: Growth performance of heritage turkeys (Journal of the Bangladesh Agricultural University, 2018)
The present study was conducted to compare the growth performance of White, Black and Bronze color type of turkeys, which have been currently introduced in Bangladesh. The birds were reared under semi-intensive system at BAU Poultry Farm with supplementation of commercial broiler grower and layer feeds. Key objectives were to investigate the growth performance of locally found turkeys (known as heritage turkeys) under semi-intensive rearing system and to recommend turkey as a supplementary part of existing poultry business in the country. A total of 46 poults of White, Black and Bronze color type unsexed birds of 5 weeks age were housed. Birds were reared under similar management conditions and feeds were purchased from local market. No significant difference (p>0.05) in live weight for three color types were found. At the end of 21 weeks rearing, Bronze type turkeys attained highest live body weight (3720.71g/bird) while White type turkeys attained lowest (3282.29g/bird). The Black type turkeys however, attained 3552.86g/bird body weight. The live weight gain was increased gradually but decreased again after 18 weeks of age. Weekly weight gains were highest in all color types at 18 weeks of age where white type male turkey attained the highest (440.71g/bird) and black type showed the lowest weight gain (345.00g/bird). No significant difference (p>0.05) in FCR among the three color types were found. Survivability under semi intensive system of three different color types, White, Black and Bronze were 100%, 88.46% and 91.67% respectively. Taken together, the growth performance of Bronze type turkey was superior to other color types used in this experiment. Therefore, it can be concluded that turkey farming will viable in Bangladesh with available local varieties under semi-intensive system through feeding of commercial broiler and layer feeds.J. Bangladesh Agril. Univ. 16(3): 471–477, December 2018